A study of the relationships of changes in pain and gait after tourniquet-induced ischemia-reperfusion in rats - Aihara, Kazuki (J Phys Ther Sci, 2017)
[Purpose] The purpose of this study was to determine the relationships of changes in pain and gait after ischemia reperfusion was induced by tourniquet in rats. [Subjects and Methods] The subjects were six ten-week-old male Wistar rats. Ischemia was induced in the left lower limbs of the experimental rats at a pressure of 300 mmHg for 90 minutes. Pain behavior evaluations were measured using the von Frey test in all the rats’ hind limbs. A consistently increasing plantar stimulus was applied until the rats exhibited an escape behavior. For the evaluation of gait, a two-dimensional motion analysis system was used to measure the distance from the calcaneus to the floor (DCF) and toe extension angle (TEA) during gait. The evaluations were performed in the normal state, 3 hours after ischemia-reperfusion, and daily until 7 days after ischemia-reperfusion. [Results] Compared with the normal state, the means of the pain threshold showed a significant decrease until 4 days after ischemia. In addition, both TEA and DCF continued to show a significant decrease at 7 days after ischemia as compared with the normal state. [Conclusion] This study revealed that hyperalgesia occurs after ischemia-reperfusion, and recovery of hyperalgesia occurred earlier than gait dysfunction recovery.